DIGITAL DRAMATURGY: PERFORMANCE ON SIMULTANEOUS VIDEO CONFERENCES IN CLASSROOM CONTEXT DURING THE COVID-19 PANDEMIC - Sepang, Nurul Robbi; Sari Monik Agustin; Rizki Fillaili (ASPIRATION Journal, 2022)
The new norm era forces people to do all activities from home, including working and studying. Data shows a significant increase in internet use during the pandemic. Longer working time, more online meetings, and sometimes they can be done at the same time (simultaneous meeting). Then, how does the Self perform if it has to be "fragmented" in one meeting or between meetings? This paper aims to identify the Self in digital dramaturgy through the performance of video conference application users in simultaneous meetings in the new normal era. This writing uses Goffman's Dramaturgy and Mead's Self as a framework with the constructionism paradigm. It uses observation and in-depth interview techniques as data collection methods. The results show that digital dramaturgy consists of preparation made at the backstage and self-performance on the front stage in a digital and non-digital setting. An interesting finding is that in live online meetings, Self appears on the front stage in the on cam (video camera is on) and mic unmutes position, but Self can be on the backstage when the cam is off (the video camera is turned off), and the mic is muted. However, when Self is in one of those situations, a third stage emerges, namely the In-between Region, where the performance is performed partly on the front stage and partly on the backstage.